2023
DOI: 10.3389/fneur.2022.955209
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial direct current stimulation for the treatment of post-stroke depression: A systematic review

Abstract: BackgroundPost-stroke depression (PSD) is not only a frequent neuropsychiatric manifestation secondary to stroke but is also associated with disability, poor rehabilitation outcomes, sleep disorders, cognitive impairment, and increased mortality. Transcranial direct current stimulation (tDCS), a primary modality of non-invasive brain stimulation (NIBS), has shown promising clinical results in the rehabilitation of patients with PSD recently. The primary aim of this systematic review is to assess the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
1
0
1
Order By: Relevance
“…De acordo com Gao et al (2023), o potencial terapêutico dos probióticos na depressão é uma área emergente de pesquisa, especialmente para pacientes resistentes aos tratamentos convencionais. Estudos recentes têm revelado uma forte conexão entre a microbiota intestinal e a depressão, destacando os probióticos como uma opção viável de tratamento adjuvante.…”
Section: Revisão Da Literaturaunclassified
“…De acordo com Gao et al (2023), o potencial terapêutico dos probióticos na depressão é uma área emergente de pesquisa, especialmente para pacientes resistentes aos tratamentos convencionais. Estudos recentes têm revelado uma forte conexão entre a microbiota intestinal e a depressão, destacando os probióticos como uma opção viável de tratamento adjuvante.…”
Section: Revisão Da Literaturaunclassified
“…Extended durations of effect can occur with rTMS when repeated daily, as post-stimulation effects can be observed up to 1 month later (Sparing and Mottaghy, 2008). A recent overview on this topic concluded that patients with PSD may benefit from rTMS but noted a high level of bias and the inability to quantitatively analyze the effect of this technique (Gao et al, 2023). In more structured studies, the stimulation of the left dorsolateral prefrontal cortex with high-frequency rTMS, compared with sham stimulation, was well tolerated and associated with a significant reduction in depression in stroke survivors (Jorge et al, 2004;Qiu et al, 2023).…”
Section: Repetitive Transcranial Magnetic Stimulationmentioning
confidence: 99%